Mobile Applications for Medication Adherence Among Diabetes Patients: A Narrative Review of Current Evidence and Future Directions - Ghozali, Muhammad Thesa (Dinasti Research, 2024)
Mobile applications (apps) have proven to be helpful tools which enable the support of diabetes patient medication adherence by providing functions for reminders tracking and educational materials. The investigation focuses on evaluating current research regarding mobile app effectiveness towards boosting medication adherence among diabetes patients. A review evaluation of research papers demonstrates the potential advantages which include superior treatment results and enhanced patient participation and blood glucose regulation abilities. The analysis includes descriptions of the application usability difficulties that patients experience alongside their preference patterns and healthcare system integration issues. The review investigates the effectiveness of individualized intervention strategies as well as the influence of real-time feedback together with provider communication that both exist within mobile apps. Clinical trials must advance and app characteristics should standardize to guarantee their positive impact on adherence across all patient types. The field requires research to build specific and easy-to-use mobile applications and artificial intelligence integration and systematic investigation of data security measures for achieving patient consent. The analysis shows encouraging value of mobile applications which enhance diabetes medication adherence yet acknowledges there must be ongoing development using evidence-based practices within this expanding mobile health sector.